Sphingosine kinase 1 as an anticancer therapeutic target - Gao Y; Gao F; Chen K; Tian ML; Zhao DL (Dove Medical Press, 2015)
Ying Gao,1,* Fei Gao,2,* Kan Chen,3,* Mei-li Tian,1 Dong-li Zhao1 1Department of Radiotherapy Oncology, First Affiliated Hospital of Xi’an Jiaotong University, 2Department of Neurology, First Affiliated Hospital of Xi’an Medical University, Xi’an, 3School of Life Sciences, Zhejiang Sci-Tech University, Hangzhou, People’s Republic of China *These authors contributed equally to this work Abstract: The development of chemotherapeutic resistance is a major challenge in oncology. Elevated sphingosine kinase 1 (SK1) levels is predictive of a poor prognosis, and SK1 overexpression may confer resistance to chemotherapeutics. The SK/sphingosine-1-phosphate (S1P)/sphingosine-1-phosphate receptor (S1PR) signaling pathway has been implicated in the progression of various cancers and in chemotherapeutic drug resistance. Therefore, SK1 may represent an important target for cancer therapy. Targeting the SK/S1P/S1PR signaling pathway may be an effective anticancer therapeutic strategy, particularly in the context of overcoming drug resistance. This review summarizes our current understanding of the role of SK/S1P/S1PR signaling in cancer and development of SK1 inhibitors. Keywords: sphingosine kinase 1, S1P, S1PR, inhibitors, cancer, therapy